The correct response is:
6x - y = 24
Write y equals one-sixth x plus 4 in standard form using integers.
(1 point)
Responses
negative lower x minus 6 lower y equals 24
negative lower x plus 6 lower y equals 24
negative lower x plus 6 lower y equals 4
6 lower x minus lower y equals 24
3 answers
explain why
In standard form, the equation of a line is written as Ax + By = C, where A, B, and C are integers and A is positive.
Given the equation y = (1/6)x + 4, we need to rearrange it to fit the standard form. To do this, we can start by multiplying every term by 6 to eliminate the fraction:
6y = (1/6)(6x) + (1/6)(24)
6y = x + 4
Now, we want to rewrite the equation in the form Ax + By = C. To do this, we can move the "x" term to the left side:
x - 6y = -4
However, in standard form, we want the coefficient of "x" to be positive. In this case, we have a negative coefficient, so we can multiply every term by -1 to make it positive:
-1(x - 6y) = -1(-4)
-x + 6y = 4
Now, the equation y = (1/6)x + 4 can be represented in standard form as -x + 6y = 4, where the coefficients and constant are integers.
Given the equation y = (1/6)x + 4, we need to rearrange it to fit the standard form. To do this, we can start by multiplying every term by 6 to eliminate the fraction:
6y = (1/6)(6x) + (1/6)(24)
6y = x + 4
Now, we want to rewrite the equation in the form Ax + By = C. To do this, we can move the "x" term to the left side:
x - 6y = -4
However, in standard form, we want the coefficient of "x" to be positive. In this case, we have a negative coefficient, so we can multiply every term by -1 to make it positive:
-1(x - 6y) = -1(-4)
-x + 6y = 4
Now, the equation y = (1/6)x + 4 can be represented in standard form as -x + 6y = 4, where the coefficients and constant are integers.